Autophagy mediates epithelial cytoprotection in eosinophilic oesophagitis. Issue 7 (16th February 2016) - Whelan, Kelly A; Merves, Jamie F; Giroux, Veronique; Tanaka, Koji; Guo, Andy; Chandramouleeswaran, Prasanna M; Benitez, Alain J; Dods, Kara; Que, Jianwen; Masterson, Joanne C; Fernando, Shahan D; Godwin, Bridget C; et al.
Abstract : Objective: The influence of eosinophilic oesophagitis (EoE)-associated inflammation upon oesophageal epithelial biology remains poorly understood. We investigated the functional role of autophagy in oesophageal epithelial cells (keratinocytes) exposed to the inflammatory EoE milieu. Design: Functional consequences of genetic or pharmacological autophagy inhibition were assessed in endoscopic oesophageal biopsies, human oesophageal keratinocytes, single cell-derived ex vivo murine oesophageal organoids as well as a murine model recapitulating EoE-like inflammation and basal cell hyperplasia. Gene expression, morphological and functional characterisation of autophagy and oxidative stress were performed by transmission electron microscopy, immunostaining, immunoblotting, live cell imaging and flow cytometry. Results: EoE-relevant inflammatory conditions promoted autophagy and basal cell hyperplasia in three independent murine EoE models and oesophageal organoids. Inhibition of autophagic flux via chloroquine treatment augmented basal cell hyperplasia in these model systems. Oesophageal keratinocytes stimulated with EoE-relevant cytokines, including tumour necrosis factor-α and interleukin-13 exhibited activation of autophagic flux in a reactive oxygen species-dependent manner. Autophagy inhibition via chloroquine treatment or depletion of Beclin-1 or ATG-7, augmented oxidative stress induced by EoE-relevant stimuli in murine EoE, oesophageal organoids and human oesophageal keratinocytes. Oesophageal epithelia of paediatric EoE patients with active inflammation displayed increased autophagic vesicle content compared with normal and EoE remission subjects. Functional flow cytometric analysis revealed autophagic flux in human oesophageal biopsies. Conclusions: Our findings reveal for the first time that autophagy may function as a cytoprotective mechanism to maintain epithelial redox balance and homeostasis under EoE inflammation-associated stress, providing mechanistic insights into the role of autophagy in EoE pathogenesis.